Sphenopalatine Ganglion Block for the Treatment of Myofascial Pain of the Head, Neck, and Shoulders. Issue 1 (January 1998) - Ferrante, F. Michael; Kaufman, Andrew G.; Dunbar, Stuart A.; Cain, Charles F.; Cherukuri, Suma
Abstract : Background and Objectives: This study examined the effectiveness of sphenopalatine ganglion block (SPGB) for myofascial pain syndrome of the head, neck, and shoulders using a double-blind, placebo-controlled, crossover study design with comparison to an internal standard consisting of trigger point injections (TPI). Methods: Patients (n = 23) were randomly assigned to receive either: (1) SPGB with 4% lidocaine, then TPI with 1% lidocaine, and finally SPGB with saline placebo or (2) SPGB with saline placebo, then TPI with 1% lidocaine, and finally SPGB with 4% lidocaine. Each respective treatment within each protocol was given sequentially at 1-week intervals for both groups. Prior to the first treatment, all patients assessed their average intensity of pain and pain at that particular moment using a visual analog pain scale. Pain intensity and pain relief were reassessed 30 minutes after each treatment and at 6 hours, 24 hours and 1 week using visual analog pain and pain relief scales. Pain intensity and pain relief data were transformed into natural logarithm units, and the statistical significance of SPGB with 4% lidocaine versus SPGB with placebo, SPGB with 4% lidocaine versus TPI, and TPI versus SPGB with placebo were tested by mixed-model analysis of variance. The magnitude of the differences in pain intensity and pain relief ratings were also compared via computation of 95% confidence intervals. Results: The analgesic effect of SPGB with 4% lidocaine was no better than placebo. Mixed-model analysis of variance revealed improved analgesia with administration of TPIs as compared to SPGB with 4% lidocaine and placebo over the entire week of observations (pain relief scores). Conclusions: This study suggests that SPGB with 4% lidocaine is no more efficacious than placebo and less efficacious than administration of standard trigger point injections in the treatment of myofascial pain of the head, neck, and shoulders.